Women and poverty: a qualitative study on selected female-headed households in Kuala Lumpur and Selangor, Malaysia - Muhamad Hilmi Abdul Rahman; Azmah Othman; Yong Zulina Zubairi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Women and poverty reduction are vital for development discourse as they determine income inequality and the inclusion rate of society. Like a global phenomenon, female-headed households in Malaysia are of great concern as they are often marginalized as the sole breadwinner, and it contributes to poverty. To investigate the challenges and factors and uncover the intricacies of social and economic resources of the issue, a qualitative case study is adopted based on a theoretical framework of social, resource, and economic theories. A purposive maximum sampling method was used in the selection of seven female-headed households in Kuala Lumpur and Selangor, Malaysia. Low educational attainment, household structure, and cost of living are three construct factors identified. It establishes a relational link considering the household head’s educational level, household structure, and rising cost of living are critical to the relationship between female headship and poverty. The contribution of this study is to question the challenges and factors linked to the concentration of poverty among households headed by females, and it elucidates a better understanding of women and poverty in Malaysia and in Southeast Asia in general. Recognizing both the unidimensional and multidimensional aspects of poverty, the implications of the study call for policy development that provides durable socio-economic support with an emphasis on the self-determination and empowerment of female headed families.